The Relationship of Knowledge About Anemia with Anemia Satus in Adolescent Women in SMA N 07 Padang - Mayasari, Novi; Devita, Hendri; Utami, Amanda Wahyu (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2022)
The prevalence of anemia among young women aged 10-18 years in Indonesia was 57.1% and 39.5% for those aged 19-45 years. The purpose of this study was to determine the relationship between knowledge about anemia and anemia status in young women at SMA 07 Padang. This type of research is an analytic study with a cross-sectional approach. The population is young girls at SMA N 7 PADANG class X and XI as many as 354 people and a sample of 53 people with a sampling technique that is random sampling. After calculating the chi-square test, it was found that p value = 0.05, which means that there is no significant relationship between knowledge about anemia and the anemia status of young women at SMA N 7 Padang. At SMA N 7 Padang, there is a sufficient level of knowledge about anemia, so it is necessary to improve health education, especially health education about anemia prevention, such as administering fe tablets regularly in collaboration with the local puskesmas work area.